Composite solid electrolyte membrane and solid-state battery

By compounding the first solid electrolyte with the second solid electrolyte whose melting point ranges from 80°C to 200°C, a composite solid electrolyte membrane is formed, which solves the problem of insufficient density of the solid-state battery electrolyte membrane and achieves higher ionic conductivity and better Good cycle performance.

CN119324249APending Publication Date: 2025-01-17QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476387.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The solid electrolyte membrane of existing solid-state batteries has poor density, which affects the transmission efficiency of lithium ions and is not conducive to inhibiting the growth of lithium dendrites.

Method used

The first solid electrolyte and the second solid electrolyte with a melting point range of 80°C to 200°C are combined to form a composite solid electrolyte membrane. The second solid electrolyte is transformed from liquid to solid to form a continuous structure to improve the density and ionic conductivity of the membrane. .

Benefits of technology

It significantly improves the density and ionic conductivity of the composite solid electrolyte membrane, improves the transmission efficiency of lithium ions, inhibits the growth of lithium dendrites, and improves the cycle performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324249A_ABST
    Figure CN119324249A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte membrane and a solid-state battery, and relates to the technical field of energy storage. The composite solid electrolyte membrane comprises a first solid electrolyte and a second solid electrolyte, and the melting point of the second solid electrolyte ranges from 80 DEG C to 200 DEG C. By compounding the first solid electrolyte and the second solid electrolyte with the melting point range of 80-200 DEG C, the compactness of the composite solid electrolyte membrane is effectively improved, and due to the fact that the second solid electrolyte has the ionic conductivity, the ionic conductivity of the composite solid electrolyte membrane can be effectively improved, and the service life of the composite solid electrolyte membrane is prolonged. Therefore, the battery using the composite solid electrolyte membrane has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a composite solid electrolyte membrane and a solid-state battery. Background Art

[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid state electrolytes (SSE) instead of flammable organic liquid electrolytes or gel electrolytes for ion transport, and have higher safety, higher energy density, faster charging speed and longer cycle life.

[0003] However, there are still some problems that need to be improved in solid-state batteries. The preparation of existing solid-state electrolyte membranes mainly involves pressing solid-state electrolyte particles into membranes. Affected by the hardness of the solid-state electrolyte particles themselves, there are gaps between the particles, resulting in poor density of the solid-state electrolyte membrane. On the one hand, this affects the transmission efficiency of lithium ions, and on the other hand, it is not conducive to inhibiting the growth of lithium dendrites. Summary of the invention

[0004] Based on this, it is necessary to provide a composite solid electrolyte membrane and a solid-state battery with higher electrolyte membrane density and higher electrolyte ion conductivity.

[0005] In a first aspect, the present application provides a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising:

[0006] a first solid electrolyte; and

[0007] The second solid electrolyte has a melting point in the range of 80°C to 200°C.

[0008] In some embodiments, the second solid electrolyte transforms from a liquid state to a solid state to form a continuous structure, and at least a portion of the first solid electrolyte is dispersed in the continuous structure of the second solid electrolyte.

[0009] In some embodiments, the porosity of the composite solid electrolyte membrane is 0.1% to 10%.

[0010] In some embodiments, the porosity of the composite solid electrolyte membrane is less than the porosity of the first composite solid electrolyte membrane;

[0011] The first composite solid electrolyte membrane includes first solid electrolyte particles and second solid electrolyte particles, and the first composite solid electrolyte membrane is formed at a temperature lower than 80°C.

[0012] In some embodiments, the surface roughness of the composite solid electrolyte membrane is 1 μm to 5 μm.

[0013] In some embodiments, the composite solid electrolyte membrane has a thickness of 10 μm to 100 μm.

[0014] In some embodiments, the ionic conductivity of the composite solid electrolyte membrane is greater than or equal to 2×10 -3 mS / cm.

[0015] In some embodiments, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal ion, and x satisfies 0<x<6.

[0016] In some embodiments, the first solid electrolyte is a halide solid electrolyte.

[0017] In some embodiments, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more of trivalent lanthanide metal ions.

[0018] In some embodiments, x satisfies 2≤x≤5.

[0019] In some embodiments, the melting point of the first solid electrolyte is greater than the melting point of the second solid electrolyte.

[0020] In some embodiments, the mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80).

[0021] In some embodiments, when the mass ratio of the first solid electrolyte to the second solid electrolyte is less than 50:50, as the mass proportion of the second solid electrolyte increases, the porosity of the composite solid electrolyte membrane decreases.

[0022] In some embodiments, the melting point of the first solid electrolyte is greater than the melting point of the second solid electrolyte.

[0023] In some embodiments, the ratio of the particle size of the first solid electrolyte to the particle size of the second solid electrolyte is (1:5) to (10:1).

[0024] In some embodiments, the first solid electrolyte includes one or more inorganic solid electrolytes.

[0025] In a second aspect, the present application also provides a solid-state battery, which includes a positive electrode, a negative electrode and the composite solid electrolyte membrane provided in the first aspect of the present application.

[0026] The above-mentioned composite solid electrolyte membrane effectively improves the density of the composite solid electrolyte membrane by adopting a composite of a first solid electrolyte and a second solid electrolyte with a melting point range of 80°C to 200°C. Since the second solid electrolyte itself has ion conductivity, it can effectively improve the ion conductivity of the composite solid electrolyte membrane, thereby making the battery using the composite solid electrolyte membrane have good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] FIG. 1 is a SEM image of the composite solid electrolyte membrane prepared in Example 1.

[0028] FIG. 2 is a SEM image of the solid electrolyte membrane prepared in Comparative Example 1. DETAILED DESCRIPTION

[0029] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0030] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0031] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0035] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, it is mentioned that the method may also include step S16, which means that step S16 may be added to the method in any order, for example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.

[0036] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0037] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0038] The current solid electrolyte membrane is limited by particles and has low density. The uneven lithium deposition / stripping caused by the uneven electric field and ion distribution at the interface can easily cause huge volume changes in lithium metal electrode materials. Local excessive lithium deposition / stripping will lead to continuous renewal of the electrolyte membrane and electrode interface, resulting in continuous interfacial reactions and continuous increase in interfacial impedance. In addition, due to the uneven deposition of lithium ions on the electrode surface, lithium dendrites can easily grow, which usually occurs on lithium metal negative electrodes. The low density of solid electrolytes causes lithium dendrites to grow through gaps, so that the lithium metal negative electrode can penetrate into the electrolyte during the lithium metal battery cycle, which may cause battery short circuits and safety hazards.

[0039] The present application provides a composite solid electrolyte membrane, which includes a first solid electrolyte and a second solid electrolyte, wherein the melting point of the second solid electrolyte ranges from 80°C to 200°C.

[0040] The above-mentioned composite solid electrolyte membrane effectively improves the density of the composite solid electrolyte membrane by adopting a composite of a first solid electrolyte and a second solid electrolyte with a melting point range of 80°C to 200°C. Since the second solid electrolyte itself has ion conductivity, it can effectively improve the ion conductivity of the composite solid electrolyte membrane, thereby making the battery using the composite solid electrolyte membrane have good cycle performance.

[0041] In some embodiments, in the composite solid electrolyte, the first solid electrolyte is in a granular state, and the second solid electrolyte is in a solid continuous state, wherein the solid continuous state is the solid continuous state obtained by converting the second solid electrolyte into a liquid state.

[0042] Specifically, the second solid electrolyte in the composite solid electrolyte is transformed from a liquid state to a solid state during the composite process of the first solid electrolyte and the second solid electrolyte.

[0043] In traditional technology, the density of solid electrolytes is improved by controlling the particle size of solid electrolyte particles and reducing the particle size, thereby reducing the interface performance between solid electrolytes and electrodes. However, reducing the particle size will lead to a decrease in the ionic conductivity of the solid electrolyte, and the improvement in density is not obvious; researchers have also tried to increase the pressing force during the preparation of solid electrolytes, but excessive pressure will damage the electrolyte particles, especially halide solid electrolyte particles, and the gaps between particles cannot be eliminated, making it difficult to commercialize.

[0044] In the composite process of the first solid electrolyte and the second solid electrolyte in the embodiment of the present application, the liquid second solid electrolyte can penetrate into the tiny gaps of the composite electrolyte system, and can be filled in the above-mentioned tiny gaps after changing from liquid to solid, overcoming the problem that the particle gaps of the existing solid electrolyte cannot be eliminated, so that the density of the composite solid electrolyte is significantly improved, thereby improving the interface performance with the electrode. At the same time, the second solid electrolyte itself has ion transmission performance, so that the composite solid electrolyte has continuous ion transmission channels everywhere, and the overall ion conductivity of the composite solid electrolyte is also guaranteed.

[0045] In some embodiments, the second solid electrolyte is transformed from an initial second solid electrolyte, and the initial state of the second solid electrolyte before compounding can be a granular dispersed phase.

[0046] In addition, the interface between the granular materials of the initial first solid electrolyte is prone to form pores and defects, while the continuous structure of the second solid electrolyte makes the composite solid electrolyte membrane more compact and uniform. Moreover, by using the first solid electrolyte and the second solid electrolyte to composite, the second solid electrolyte can provide a stable matrix and effective ion conduction channel for the dispersed first solid electrolyte, which not only effectively reduces the porosity of the composite solid electrolyte membrane and improves the density of the composite solid electrolyte membrane, but also further improves the ion conductivity of the prepared composite solid electrolyte membrane.

[0047] In some embodiments, the porosity of the composite solid electrolyte membrane is 0.1% to 10%. Specifically, the porosity of the composite solid electrolyte membrane may be, but is not limited to, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. In this way, by using a first solid electrolyte and a second solid electrolyte with a melting point range of 80°C to 200°C, the porosity of the composite solid electrolyte membrane is effectively reduced. And by controlling the porosity to be within the range of 0.1% to 10%, while improving the compactness, lithium ions can still be effectively conducted through the pores of the membrane, so that the battery using the composite solid electrolyte membrane has good electrochemical properties. Further, the porosity of the composite solid electrolyte membrane may be 0.3% to 6%, more preferably 0.5% to 3%.

[0048] In some embodiments, the porosity of the composite solid electrolyte membrane is less than that of the first composite solid electrolyte membrane, and the first composite solid electrolyte membrane is a composite solid electrolyte membrane formed by pressing the first solid electrolyte and the second solid electrolyte at a temperature lower than the melting point of the second solid electrolyte. In this way, the second solid electrolyte remains in a solid state during the preparation of the first composite solid electrolyte membrane, and the composite solid electrolyte membrane of the embodiment of the present application has a lower porosity and a higher density than the first composite solid electrolyte membrane.

[0049] In some embodiments, the surface roughness of the composite solid electrolyte membrane is 1 μm to 5 μm, and the surface roughness of the composite solid electrolyte membrane can be, but is not limited to, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or 5 μm, etc. In this way, by using a first solid electrolyte and a second solid electrolyte with a melting point range of 80°C to 200°C, the surface roughness of the composite solid electrolyte membrane is effectively reduced. And the surface roughness of the composite solid electrolyte membrane is controlled within the above range, and the composite solid electrolyte membrane can be well combined with the electrode-level sheet when combined, optimizing the interface problem between the electrode sheet and the solid electrolyte membrane.

[0050] In some embodiments, the second solid electrolyte comprises Li3MCl 6-x Brx , M is a trivalent metal ion, and x satisfies 0<x<6.

[0051] The second solid electrolyte of the embodiment of the present application includes a solid electrolyte obtained by doping and modifying the Li3MCl6 basic halide solid electrolyte with the halogen element Br. By replacing some chloride ions in Li3MCl6 with bromide ions with lower electronegativity and larger ionic radius, the strength of the ionic bond can be weakened, and the melting point of the electrolyte material can be reduced, so that the initial second solid electrolyte of the raw material can be partially or completely melted at a lower temperature (80°C~200°C) to form a continuous state, and then a second solid electrolyte with a continuous structure is formed after phase change and solidification.

[0052] In addition, bromide ions with a larger ionic radius replace some chloride ions in the electrolyte, increase the voids in the lattice or reduce the rigidity of the lattice, reduce the constraints on lithium ions, thereby facilitating the migration of lithium ions and improving the ionic conductivity of the composite solid electrolyte membrane. Bromide ions also have lower electronegativity, which helps to reduce side reactions between the electrolyte and the electrode material, thereby improving the stability of the interface and extending the cycle life of the solid-state battery using the composite solid electrolyte.

[0053] In some embodiments, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more of trivalent lanthanide metal ions, and 2≤x≤5.

[0054] It should be noted that M may include one metal ion or multiple metal ions. For example, M includes two metal ions, assuming that they are A ions and B ions, and the second solid electrolyte may be Li3A y B z Cl 6-x Br x , the valence of element A is a, the valence of element B is b, and they satisfy ay+bz=3.

[0055] As an example, the second solid electrolyte is not limited to Li3Y 0.5 Dy 0.5 Cl3Br3、Li3Y 0.5 Dy 0.5 Cl4Br2、Li3Y 0.5 Dy 0.5 Cl5Br1、Li3Y 0.5 Dy 0.5 Cl2Br4、Li3Y 0.5 Dy0.5 Cl1Br5、Li3Y 0.5 Fe 0.5 Cl1Br5、Li3Dy 0.5 Al 0.5 One or more of Cl1Br5. Preferably, the second solid electrolyte comprises Li3Y 0.5 Dy 0.5 Cl3Br3.

[0056] In some embodiments, the first solid electrolyte includes, but is not limited to, one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte. Preferably, the first solid electrolyte may include a halide solid electrolyte material, and a halide solid electrolyte material with high flexibility and excellent deformation ability may be preferably selected.

[0057] As an example, the halide solid electrolyte material includes Li 1.75 ZrCl 4.75 O 0.5 , Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 Thus, during the composite process of the first solid electrolyte and the second solid electrolyte, the first solid electrolyte can achieve better and tighter fit with the continuous structure of the second solid electrolyte, further improving the density of the composite solid electrolyte layer.

[0058] In some embodiments, the melting point of the first solid electrolyte is greater than the melting point of the second solid electrolyte. In this way, during the composite process of the first solid electrolyte and the second solid electrolyte, the second solid electrolyte is transformed into a liquid phase with fluidity via the initial second solid electrolyte of the granular dispersed phase, and then transformed from liquid to solid to form a continuous structure. The first solid electrolyte can remain solid throughout the composite process, and it can provide mechanical support and reasonable porosity for the entire composite structure, and maintain sufficient ion channels. Moreover, during the composite process, the second solid electrolyte in liquid form can effectively penetrate into the microstructure of the solid first solid electrolyte, enhance the bonding force between the two, and thus improve the overall performance of the composite solid electrolyte membrane.

[0059] In some embodiments, the mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80), including but not limited to (95:5), (90:10), (85:15), (80:20), (75:25), (70:30), (65:35), (60:40), (55:45), (50:50), (45:55), (40:60), (35:65), (30:70), (25:75) or (20:80. Preferably, the mass ratio of the first solid electrolyte to the second solid electrolyte can be (80:20) to (35:65). More preferably, the mass ratio of the first solid electrolyte to the second solid electrolyte can be (70:30) to (45:55).

[0060] Furthermore, when the mass ratio of the first solid electrolyte to the second solid electrolyte is less than 50:50, as the mass proportion of the second solid electrolyte increases, the porosity of the composite solid electrolyte membrane decreases. Thus, when the mass ratio of the first solid electrolyte to the second solid electrolyte is less than 50:50, as the mass proportion of the second solid electrolyte increases, more second solid electrolytes form a continuous solid structure, thereby reducing the overall porosity of the composite solid electrolyte membrane. By controlling the porosity of the composite solid electrolyte membrane within a reasonable range through the mass ratio of the first solid electrolyte to the second solid electrolyte, the composite solid electrolyte membrane can maintain good ionic conductivity while increasing density.

[0061] In some embodiments, the ionic conductivity of the second solid electrolyte is greater than or equal to 2×10 -3 mS / cm. The ionic conductivity of the second solid electrolyte may be, but is not limited to, 1.5mS / cm, 1.6mS / cm, 1.7mS / cm, 1.8mS / cm, 1.9mS / cm, 2.0mS / cm, 2.1mS / cm, 2.2mS / cm, 2.3mS / cm, 2.4mS / cm, 2.5mS / cm, 2.6mS / cm or 2.7mS / cm. In this way, it can be ensured that the composite solid electrolyte membrane obtained by adding the second solid electrolyte has good ionic conductivity.

[0062] In some embodiments, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:5) to (10:1), including but not limited to (1:5), (1:4), (1:3), (1:2), (1:1), (2:1), (3:1), (4:1), (5:1), (6:1), (7:1), (8:1), (9:1) or (10:1). Preferably, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:2) to (6:1), and more preferably, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (2:1) to (4:1). In this way, compared with the second solid electrolyte, the particle size of the first solid electrolyte is within a suitable range, and the first solid electrolyte can be more effectively and evenly dispersed in the continuous structure of the second solid electrolyte. Compared with the first solid electrolyte, the particle size of the second solid electrolyte is within a suitable range, and the second solid electrolyte can melt faster and enter the gaps of the first solid electrolyte.

[0063] Next, the solid-state battery provided in the second aspect of the embodiment of the present application is described, and the solid-state battery includes a positive electrode, a composite solid electrolyte membrane provided in the first aspect of the embodiment of the present application, and a negative electrode. Applying the composite solid electrolyte membrane provided in the first aspect of the embodiment of the present application to a lithium metal solid-state battery can effectively improve the cycle stability of the lithium metal solid-state battery, inhibit lithium dendrites from passing through the composite solid electrolyte membrane, and can also improve the battery capacity and cycle performance.

[0064] According to the solid-state battery of the second aspect of the embodiment of the present application, there is no particular restriction on the specific type of the positive electrode sheet, and it can be selected according to actual needs. For example, the positive electrode may include a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer contains a positive electrode active material, a conductive agent and a binder. The positive electrode active material may be lithium cobalt oxide (LCO), the conductive agent may be vapor-grown carbon fiber (VGCF), and the binder may be polytetrafluoroethylene (PTFE). The negative electrode may include a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer contains a negative electrode active material, a conductive agent and a binder. The negative electrode active material may be graphite, the conductive agent may be vapor-grown carbon fiber (VGCF), and the binder may be polytetrafluoroethylene (PTFE).

[0065] In order to explain the technical content, structural features, achieved objectives and effects of the technical solutions of the embodiments of the present application in detail, the following is a detailed description in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0066] Example 1

[0067] A composite solid electrolyte membrane, comprising a first solid electrolyte Li 2.25Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 , and the second solid electrolyte Li3Y 0.5 Dy 0.5 Cl3Br3, wherein the second solid electrolyte transforms from liquid to solid to form a continuous phase, the melting point of the first solid electrolyte is 350°C, the melting point of the second solid electrolyte is 120°C, the ionic conductivity of the second solid electrolyte is 2.72mS / cm, the mass ratio of the first solid electrolyte to the second solid electrolyte is 1:1, and the particle size D50 ratio of the first solid electrolyte to the second solid electrolyte is 3:1.

[0068] (1) Preparation of positive electrode

[0069] NCM811, PTFE, super-P, and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, and formed a first mixed material, which was rolled to form a first positive electrode layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the first positive electrode layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the time was 10 minutes, and the pressure was 120Mpa.

[0070] (2) Preparation of negative electrode

[0071] The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a second mixture, which is then rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa.

[0072] (3) Preparation of composite solid electrolyte membrane

[0073] The first solid electrolyte particles and the second solid electrolyte particles are mixed by mass, and then subjected to heat pressing and cooled to form a composite solid electrolyte membrane.

[0074] The temperature of the hot pressing treatment is greater than the melting point of the second solid electrolyte, and the temperature of the hot pressing treatment can be 80°C to 200°C. The temperature of the hot pressing treatment can be, but is not limited to, 80°C, 100°C, 120°C, 140°C, 150°C, 160°C, 180°C or 200°C. In this way, the hot pressing treatment can ensure that Li3MCl 6-x Brx Furthermore, in Example 1 and the following Examples 2 to 9 and Comparative Examples 1 to 3, the hot pressing temperature is selected to be 140°C.

[0075] The time of hot pressing treatment is 0.5 min to 30 min, including but not limited to 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 8 min, 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 25 min or 30 min. 6-x Br x It can flow within a certain time and has a suitable flow range to ensure the conductivity of lithium ions. Further, in Example 1 and the following Examples 2 to 9 and Comparative Examples 1 to 4, the hot pressing time is selected to be 15 minutes.

[0076] The pressure of the hot pressing treatment is 10 MPa to 500 MPa, including but not limited to 10 MPa, 20 MPa, 50 MPa, 80 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa or 500 MPa. In this way, the hot pressing pressure can promote the Li3MCl 6-x Br x The first solid electrolyte can flow without affecting the structure of the first solid electrolyte. Further, in Example 1 and the following Examples 2 to 9 and Comparative Examples 1 to 4, the pressure of the hot pressing treatment is selected to be 250 MPa.

[0077] (4) Preparation of solid-state batteries

[0078] The positive electrode sheet, the composite solid electrolyte membrane and the negative electrode sheet are bonded together to obtain a solid-state battery.

[0079] Example 2

[0080] The composite solid electrolyte membrane of Example 2 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0081] The second solid electrolyte is Li3Y 0.5 Dy 0.5 Cl4Br2, the melting point of the second solid electrolyte is 124°C, and the ionic conductivity of the second solid electrolyte is 2.13 mS / cm.

[0082] Example 3

[0083] The composite solid electrolyte membrane of Example 3 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0084] The second solid electrolyte is Li3Y 0.5 Dy 0.5 Cl1Br5, the melting point of the second solid electrolyte is 126°C, and the ionic conductivity of the second solid electrolyte is 1.95 mS / cm.

[0085] Example 4

[0086] The composite solid electrolyte membrane of Example 4 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0087] The second solid electrolyte is Li3Y 0.5 Fe 0.5 Cl1Br5, the melting point of the second solid electrolyte is 125°C, and the ionic conductivity of the second solid electrolyte is 2.45 mS / cm.

[0088] Example 5

[0089] The composite solid electrolyte membrane of Example 5 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0090] The second solid electrolyte is Li3Dy 0.5 Al 0.5 Cl1Br5, the melting point of the second solid electrolyte is 128°C, and the ionic conductivity of the second solid electrolyte is 2.16mS / cm.

[0091] Example 6

[0092] The composite solid electrolyte membrane of Example 6 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0093] The mass ratio of the first solid electrolyte to the second solid electrolyte is 95:5.

[0094] Example 7

[0095] The composite solid electrolyte membrane of Example 7 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0096] The mass ratio of the first solid electrolyte to the second solid electrolyte is 20:80.

[0097] Example 8

[0098] The composite solid electrolyte membrane of Example 8 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0099] The first solid electrolyte is Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0100] Example 9

[0101] The composite solid electrolyte membrane of Example 9 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0102] The first solid electrolyte is Li7La3Zr2O 12 .

[0103] Comparative Example 1

[0104] The electrolyte membrane of Comparative Example 1 is different from the composite solid electrolyte membrane of Example 1 in that:

[0105] The addition of the second solid electrolyte was omitted, and the rest was the same as in Example 1, that is, the electrolyte membrane of Comparative Example 1 included the first solid electrolyte but did not include the second solid electrolyte, and the mass proportion of the first solid electrolyte was 100%.

[0106] Comparative Example 2

[0107] The composite solid electrolyte membrane of Comparative Example 2 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0108] The second solid electrolyte is Li3Y 0.5 Dy 0.5 Cl6, the melting point of the second solid electrolyte is 330°C, and the ionic conductivity of the second solid electrolyte is 1.28 mS / cm.

[0109] Comparative Example 3

[0110] The composite solid electrolyte membrane of Comparative Example 3 is substantially the same as the composite solid electrolyte membrane of Example 1, except that:

[0111] The second solid electrolyte is Li3Y 0.5 Dy 0.5 Br6, the melting point of the second solid electrolyte is 330°C, and the ionic conductivity of the second solid electrolyte is 1.53 mS / cm.

[0112] Comparative Example 4

[0113] The difference between Comparative Example 4 and Example 1 is that in the preparation of the composite solid electrolyte membrane, the first solid electrolyte particles and the second solid electrolyte particles are mixed by mass, and then pressed to form the composite solid electrolyte membrane at a pressing temperature of 60°C.

[0114] The relevant materials and condition parameters in Examples 1 to 11 and Comparative Examples 1 to 4 are shown in Table 1 below, where “-” means untreated.

[0115] Table 1

[0116]

[0117] The solid electrolyte membranes of the above-mentioned embodiments 1 to 9 or comparative examples 1 to 4 and the corresponding solid-state lithium metal batteries were subjected to performance tests, and the test results are shown in Table 2 below, wherein the test conditions or test standards for each performance test item are as follows:

[0118] (1) Porosity test

[0119] True density test: The true density of the composite positive electrode is obtained by testing with a true density meter. The test process is as follows: After the power is turned on, the instrument is preheated according to the requirements of the instrument manual to ensure that the instrument reaches a stable working state. Place the sample to be tested in the sample pool, press the measurement button, and the instrument will automatically measure the density. After the measurement is completed, the instrument will automatically record the data and calculate the true density value ρ 真 .

[0120] Compacted density test: Add 100 mg of powder into a φ10 mm mold, apply a pressure of 375 MPa and maintain the pressure for 3 minutes, then remove the mold to obtain a compacted sheet, measure its thickness, and calculate its compacted density ρ 压实 .

[0121] Porosity: Porosity is (ρ 真 -ρ 压实 ) / ρ 真 .

[0122] (2) Surface roughness test

[0123] The solid electrolyte membrane is placed under a high-precision optical microscope for observation. In the 3D imaging mode, the electrolyte sheet can be obtained at 200*300μm 2 The surface height distribution information inside the solid electrolyte membrane can be obtained by counting the maximum surface height difference of the solid electrolyte membrane.

[0124] (3) Melting point test

[0125] The solid electrolyte material was placed in a crucible and heated from 30°C to 300°C at a rate of 10°C / min in a nitrogen atmosphere to measure the melting point of the solid electrolyte material.

[0126] (4) Thickness test

[0127] According to GB / T 6672-2001 standard, a Millimar film thickness gauge (Millimar C1208, Millimar, Germany) was used to measure the thickness of the composite solid electrolyte membrane in the examples and comparative examples.

[0128] (5) Electrolyte membrane conductivity test

[0129] At 25°C, the test structure of stainless steel sheet / solid electrolyte membrane / stainless steel sheet was used, the frequency range was 0.1Hz-7MHz, and the AC signal amplitude Z was 10 -2 The AC impedance test was carried out under the condition of V, and the ionic conductivity was calculated according to the formula σ=L / (S*R), where L is the thickness of the solid electrolyte membrane, S is the cross-sectional area of ​​the solid electrolyte membrane, and R represents the charge transfer resistance.

[0130] (6) Discharge specific capacity test

[0131] The solid-state lithium metal batteries in the examples and comparative examples were tested for capacity. The batteries were left to stand for 1 min and discharged at a discharge current of 0.1 C until the cut-off voltage reached 2.7 V, and the first discharge capacity was recorded.

[0132] (7) Cyclic performance test

[0133] The solid-state lithium metal batteries in the embodiments and comparative examples were subjected to a cycle test. At a temperature of 25°C±2°C, in the first step, they were charged at 0.1C to a final voltage of 4.5V, a cutoff current of 0.05C, and allowed to stand for 30 minutes; in the second step, they were discharged at 0.1C to a final discharge voltage of 2.7V, the discharge capacity was recorded, and the battery was allowed to stand for 30 minutes; the first and second steps were repeated to test the cycle performance of the battery for 100 cycles.

[0134] Table 2

[0135]

[0136] Combining Table 1 and Table 2, as well as Figure 1 and Figure 2, it can be seen that the porosity and surface roughness of Examples 1 to 7 are significantly lower than those of Comparative Examples 1 to 4, and the conductivity of the composite solid electrolyte membrane of Examples 1 to 7 and the capacity retention rate after 100 cycles are significantly higher than those of Comparative Examples 1 to 4, indicating that compared with Comparative Examples 1-4, in Examples 1 to 11, during the composite process of the first solid electrolyte and the second solid electrolyte, the liquid second solid electrolyte can penetrate into the tiny gaps of the composite electrolyte system, and can be filled in the above-mentioned tiny gaps after changing from a liquid state to a solid continuous state, overcoming the problem that the particle gaps of the existing solid electrolyte cannot be eliminated, so that the compactness of the composite solid electrolyte is significantly improved, thereby improving the interface performance with the pole piece. At the same time, the second solid electrolyte itself has ion transmission performance, so that the composite solid electrolyte has continuous ion transmission channels everywhere, and the overall ion conductivity of the composite solid electrolyte is also guaranteed, so that the capacity and cycle performance of the solid-state battery prepared by the composite solid electrolyte membrane are optimized.

[0137] The porosity and surface roughness of Examples 1 to 7 are better than those of Examples 8 and 9. The possible reason is that the first solid electrolyte in Examples 8 and 9 is an oxide solid electrolyte. Compared with the halide solid electrolyte, the oxide solid electrolyte is hard and has a higher Young's modulus. During the hot pressing process, the oxide solid electrolytes have more gaps between them and have worse contact with the second solid electrolyte than the halide solid electrolyte. Therefore, when the mass proportion of the second solid electrolyte in the system is the same, the porosity and surface roughness of Examples 8 and 9 are worse than those of Examples 1 to 7.

[0138] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0139] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A composite solid electrolyte membrane, characterized in that: include: The first solid-state electrolyte; and The second solid electrolyte has a melting point in the range of 80°C to 200°C.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The porosity of the composite solid electrolyte membrane is 0.1% to 10%.

3. The composite solid electrolyte membrane according to claim 1, characterized in that: The porosity of the composite solid electrolyte membrane is less than the porosity of the first composite solid electrolyte membrane; The first composite solid electrolyte membrane includes first solid electrolyte particles and second solid electrolyte particles, and the first composite solid electrolyte is formed at a temperature lower than 80°C.

4. The composite solid electrolyte membrane according to claim 1, characterized in that: The surface roughness of the composite solid electrolyte membrane is 1 μm to 5 μm.

5. The composite solid electrolyte membrane according to claim 1, characterized in that: The second solid electrolyte includes Li3MCl 6-x Br x , M is a trivalent metal ion, and x satisfies 0<x<6; Preferably, the first solid electrolyte is a halide solid electrolyte.

6. The composite solid electrolyte membrane according to claim 5, characterized in that: M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3 + Sc 3+ 、Bi 3+ and one or more trivalent lanthanide metal ions, 2≤x≤5.

7. The composite solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80).

8. The composite solid electrolyte membrane according to claim 1 or 7, characterized in that: When the mass ratio of the first solid electrolyte to the second solid electrolyte is less than 50:50, as the mass proportion of the second solid electrolyte increases, the porosity of the composite solid electrolyte membrane decreases.

9. The composite solid electrolyte membrane according to claim 1, characterized in that: The melting point of the first solid electrolyte is greater than the melting point of the second solid electrolyte.

10. A solid-state battery, characterized in that The battery comprises a positive electrode, a negative electrode and the composite solid electrolyte membrane according to any one of claims 1 to 9.